Migração Brasileira em Portugal: retornar ao Brasil ou permanecer em Portugal? / Brazilian Migration in Portugal: back to Brazil or stay in Portugal? - da Silva, Romerito Valeriano; Fernandes, Duval Magalhães; Peixoto, João (Caderno de Geografia, 2018)
A crise internacional de 2008 foi uma perturbação do subsistema migratório luso-brasileiro que provocou diferentes reações nos brasileiros: alguns retornaram ao Brasil e outros permaneceram em Portugal. Por meio de uma perspectiva geográfica, procura-se compreender por que os imigrantes brasileiros, tendo vivido no mesmo contexto espaço-temporal em Portugal, reagiram de forma diferente à perturbação desse subsistema migratório. Para isso, foram realizadas 125 entrevistas estruturadas, sendo 60 com brasileiros que viviam em Portugal e retornaram ao Brasil e 65 com brasileiros que permaneceram em Portugal. Os resultados permitiram traçar as diferenças no perfil e nas condições de vida antes e durante a emigração dos brasileiros que retornaram e dos que permaneceram em Portugal, bem como discutir as razões para o retorno e para a permanência. Palavras-chave: Geografia da População, migração internacional, movimento de retorno, Portugal, Brasil. Abstract The international crisis of 2008 led to a disturbance of the Luso-Brazilian migratory subsystem and to different reactions of Brazilians: some returned to Brazil, whilst others remained in Portugal. Based on a geographical perspective, an attempt has made to understand the reasons why Brazilian immigrants, having lived in the same spatial and temporal context in Portugal, reacted differently to the disturbance of this migratory subsystem. Thus, 125 structured interviews have conducted: 60 participants were Brazilians who were living in Portugal and returned to Brazil, and 65 were Brazilians who decided to remain in Portugal. The results allowed us to outline the differences in Brazilians’ profile and living conditions before and during emigration of both those who returned home and those who remained in Portugal, as well as to discuss the reasons behind their returning and staying, respectively. Keywords: Population geography, international migration, migratory return movements, Portugal, Brazil.